Geoinformatics and methods of studying natural systems in agriculture - Pluzhnikova Natalya N. (BIO Web of Conferences, 2023)
The development of information systems has led to interdisciplinary approaches in the field of studying the agricultural crops cultivation. The author analyzes the role of such an interdisciplinary field as geoinformatics in the field of agricultural cultivation and, in particular, viticulture. The author points out the systematic nature of this field study, its applied nature, the need to train high-quality specialists. The author presents a number of geoinformatics methods and tools that can be applied in viticulture. Geoinformatics methods allow to perform soil and climate analysis, develop measures to protect vineyards from weather conditions. The author comes to the conclusion that geoinformatics methods can be used to optimize various viticulture processes, from growing and caring for vines to harvesting, marketing, and resource management at the level of modern agricultural product quality requirements.